2014
DOI: 10.1002/jcu.22245
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic findings of localized Castleman disease of the abdomen and pelvis

Abstract: Localized Castleman disease in the abdomen and pelvis usually appears on US as a heterogeneously hypoechoic lesion containing thin septa, and more commonly than not, demonstrates posterior acoustic enhancement and marked vascularity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Castleman disease, alternatively known as giant lymph node hyperplasia, is rarely localized in the adrenal glands . In previous reports, the lesions were hypoechoic and solid . We found that Castleman disease lesions in the abdomen and pelvis usually appeared as well‐demarcated homogeneous hypoechoic masses, with no vascularization.…”
Section: Discussionsupporting
confidence: 91%
“…Castleman disease, alternatively known as giant lymph node hyperplasia, is rarely localized in the adrenal glands . In previous reports, the lesions were hypoechoic and solid . We found that Castleman disease lesions in the abdomen and pelvis usually appeared as well‐demarcated homogeneous hypoechoic masses, with no vascularization.…”
Section: Discussionsupporting
confidence: 91%
“… 15 Ultrasound is particularly useful for guiding percutaneous biopsy. 16 MR imaging would likely not add any substantial new information beyond that provided by CT.…”
Section: Discussionmentioning
confidence: 99%
“…Internal echoes are homogeneous or not, and may be accompanied by fine strong echo separation or calcification. Most of the posterior echo is enhanced, with abundant feeding vessels in color doppler [ 5 , 6 ]. Generally speaking, the case we reported is similar to existing record in the literature.…”
Section: Discussion/conclusionmentioning
confidence: 99%